2008
DOI: 10.1111/j.1469-1809.2008.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Four SNPS on Chromosome 9p21 Confer Risk to Premature, Familial CAD and MI in an American Caucasian Population (GeneQuest)

Abstract: SummaryGenome-wide association studies have separately identified four single nucleotide polymorphisms (SNPs) on chromosome 9p21 that confer susceptibility to coronary artery disease (CAD) and myocardial infarction (MI). This study presents the first analysis of these SNPs (rs10757274, rs2383206, rs2383207, and rs10757278) in a premature, familial CAD/MI population (GeneQuest). We performed a case-control analysis of the GeneQuest Caucasian population with 310 cases with premature CAD and MI (average age at on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 11 publications
3
53
0
Order By: Relevance
“…In 2007, independent genome-wide association studies revealed nine highly correlated SNPs (r 2 > 0.8) in a new locus in the region of chromosome 9 (9p21.3), showing the greatest association with heterogeneous CAD of all of the loci analyzed so far (Helgadottir et al, 2007;McPherson et al, 2007;Samani et al, 2007). Since then, numerous studies have confirmed the association of this locus with CAD or myocardial infarction (MI) in populations of European origin (Abdullah et al, 2008;Anderson et al, 2008;Assimes et al, 2008;Lemmens et al, 2009;Koch et al, 2011) as well as Eastern (Shen et al, 2008a;Ding et al, 2009) and Southern Asia origin (AshokKumar et al, 2011). However, genetic heterogeneity was shown in Black subjects (Assimes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, independent genome-wide association studies revealed nine highly correlated SNPs (r 2 > 0.8) in a new locus in the region of chromosome 9 (9p21.3), showing the greatest association with heterogeneous CAD of all of the loci analyzed so far (Helgadottir et al, 2007;McPherson et al, 2007;Samani et al, 2007). Since then, numerous studies have confirmed the association of this locus with CAD or myocardial infarction (MI) in populations of European origin (Abdullah et al, 2008;Anderson et al, 2008;Assimes et al, 2008;Lemmens et al, 2009;Koch et al, 2011) as well as Eastern (Shen et al, 2008a;Ding et al, 2009) and Southern Asia origin (AshokKumar et al, 2011). However, genetic heterogeneity was shown in Black subjects (Assimes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen studies were based in Europe or the United States, [1][2][3][4][5][17][18][19][20][21][22][23][24][25][26][27][28][29][30] 6 in East Asia, [31][32][33][34][35][36] and 1 in North Africa. 37 Of these studies, 5 were prospective, 17 …”
Section: Meta-analysismentioning
confidence: 99%
“…Nineteen studies were based in Europe or the United States, 1-5,17-30 6 in East Asia, 31-36 and 1 in North Africa. 37 Of these studies, 5 were prospective, 17,21,25,28,30 2 were nested case-control, 22,29 and 19 were retrospective case-control studies. Five studies included only patients with MI, whereas 21 included patients with MI or coronary stenosis (defined by intervention procedures).…”
mentioning
confidence: 99%
“…4 The finding has led to a plethora of further studies that have largely confirmed the association of the 9p21 locus with CAD and MI in both case-control and cohort studies and in multiple ethnic groups. [5][6][7][8][9][10][11][12] 9p21 represents the most replicated locus for CAD and MI to date. The risk allele as currently defined, until causal variants are identified, is common (allele frequency of almost 50%) and associated with a 20% to 30% increased risk per copy.…”
mentioning
confidence: 99%